1993
DOI: 10.1590/s0102-311x1993000400002
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização da demanda de pacientes com carcinoma de colo uterino no Hospital das Clínicas da Universidade Federal de Uberlândia, Minas Gerais, Brasil, 1984-1988

Abstract: Foi realizado um estudo retrospectivo de 180 casos de carcinoma de colo uterino internados no Hospital das Clínicas da Universidade Federal de Uberlândia, no período de 1984 a 1988, segundo variáveis pessoais e de tempo. Encontrou-se um aumento gradativo com o tempo e uma maior freqüência entre 35 e 60 anos de idade. Aproximadamente 51% das pacientes eram provenientes de outras cidades e estados. Verificou-se uma maior freqüência em multíparas e em mulheres que iniciaram sua vida sexual antes dos 20 anos. Gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
(3 reference statements)
0
1
0
1
Order By: Relevance
“…The effect of exposures is additive over time; therefore, age is directly correlated with cervical cancer risk 1,3 . Several studies have shown that women who are older, have high-grade intraepithelial lesions, are black-or brown-skinned, have a history of multiple pregnancies, became sexually active at a young age, have had more sexual partners, or come from a low socioeconomic background are more likely to have cervical cancer and treatment failure 12,14,15,16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…The effect of exposures is additive over time; therefore, age is directly correlated with cervical cancer risk 1,3 . Several studies have shown that women who are older, have high-grade intraepithelial lesions, are black-or brown-skinned, have a history of multiple pregnancies, became sexually active at a young age, have had more sexual partners, or come from a low socioeconomic background are more likely to have cervical cancer and treatment failure 12,14,15,16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…Gomes CHR, Silva JA, Ribeiro JA, Penna RMM Revista Brasileira de Cancerologia 2012; 58(1):41-45 INTRODUÇÃO a neoplasia maligna do colo uterino é a terceira em incidência entre as femininas e responsável por cerca de 275 mil óbitos/ano no mundo, segundo dados de 2008 [1][2] , sendo alvo de grande preocupação por parte dos órgãos de saúde pública. é duas vezes mais frequente em países subdesenvolvidos devido à presença de fatores de risco como a frequência aumentada de exposição ao Papilomavírus humano (HPV) pela iniciação sexual precoce e multiplicidade de parceiros sexuais, além de outros como multiparidade, tabagismo, hábitos de higiene precários, subnutrição e acesso dificultoso aos serviços de saúde [3][4] .…”
unclassified